The effects of a wellness education program and wellness locus of control upon wellness behaviors of middle school students - Graff, Dawn. (My University, 1981)
This study examined change in wellness behavior among middle school students following a wellness education program. The Children's Wellness Behavior Inventory (CWBI) was designed to measure this change. Effects of wellness locus of control upon wellness behavior change were also examined.The Children's Wellness Locus of Control Inventory (CWLC) was developed to determine wellness locus of control orientation. Subjects were 80 5th and 6th graders attending Onalaska Middle School, Onalaska, Wisconsin. This study called for a pretest to post-test experimental design and involved three groups. The experimental group (N=23) participated in a six-weeks wellness education program between pre and post-tests. The non-relevant treatment group (N=26) participated in a six-week first aid program between pre and post-tests. The Mann-Whitney U- test was used to determine significance of wellness behavior change.
Keywords: Health education (Elementary) -- Wisconsin -- Onalaska; Onalaska Middle School (Onalaska, Wis.) -- Students -- Attitudes